New fossil remains of Fusuisaurus zhaoi (Sauropoda: Titanosauriformes) from the Lower Cretaceous of Guangxi, southern China. (May 2020) - Mo, Jinyou; Li, Jincheng; Ling, Yunchuan; Buffetaut, Eric; Suteethorn, Suravech; Suteethorn, Varavudh; Tong, Haiyan; Cuny, Gilles; Amiot, Romain; Xu, Xing
Abstract: We describe a large, nearly completely preserved sauropod humerus from the Lower Cretaceous Xinlong Formation of Napai Basin, Fusui County, Guangxi Zhuang Autonomous Region, southern China. It was excavated from the quarry that produced the holotypic specimen of the titanosauriform Fusuisaurus zhaoi . With a preserved length of 183.5 cm, the newly collected humerus is tentatively referred to and supports a giant size of Fusuisaurus zhaoi, which increases our knowledge of the diversity of giant titanosauriforms from the late Early Cretaceous of Asia.